Genetic characterization and estimated 4CMenB vaccine strain coverage of 284 Neisseria meningitidis isolates causing invasive meningococcal disease in Argentina in 2010–2014 - Adriana Efron; Alessandro Brozzi; Alessia Biolchi; Margherita Bodini; Maria Giuliani; Silvia Guidotti; Federico Lorenzo; María Alicia Moscoloni; Alessandro Muzzi; Florencia Nocita; Mariagrazia Pizza; Rino Rappuoli; et al. (Human Vaccines & Immunotherapeutics)
Meningococcal (Neisseria meningitidis) serogroup B (MenB) strain antigens are diverse and a limited number of strains can be evaluated using the human serum bactericidal antibody (hSBA) assay. The genetic Meningococcal Antigen Typing System (gMATS) was developed to predict the likelihood of coverage for large numbers of isolates by the 4CMenB vaccine, which includes antigens Neisseria adhesin A (NadA), Neisserial Heparin-Binding Antigen (NHBA), factor H-binding protein (fHbp), and Porin A (PorA). In this study, we characterized by whole-genome analyses 284 invasive MenB isolates collected from 2010 to 2014 by the Argentinian National Laboratories Network (52–61 isolates per year). Strain coverage was estimated by gMATS on all isolates and by hSBA assay on 74 randomly selected isolates, representative of the whole panel. The four most common clonal complexes (CCs), accounting for 81.3% of isolates, were CC-865 (75 isolates, 26.4%), CC-32 (59, 20.8%), CC-35 (59, 20.8%), and CC-41/44 (38, 13.4%). Vaccine antigen genotyping showed diversity. The most prevalent variants/peptides were fHbp variant 2, NHBA peptides 24, 21, and 2, and PorA variable region 2 profiles 16–36 and 14. The nadA gene was present in 66 (23.2%) isolates. Estimated strain coverage by hSBA assay showed 78.4% of isolates were killed by pooled adolescent sera, and 51.4% and 64.9% (based on two different thresholds) were killed by pooled infant sera. Estimated coverage by gMATS (61.3%; prediction interval: 55.5%, 66.7%) was consistent with the infant hSBA assay results. Continued genomic surveillance is needed to evaluate the persistence of major MenB CCs in Argentina.